1996
DOI: 10.1097/00005392-199607000-00047
|View full text |Cite
|
Sign up to set email alerts
|

Oral Fleroxacin Prophylaxis in Transurethral Surgery

Abstract: The oral administration of 1 daily tablet of fleroxacin for the duration of catheterization is a safe, efficacious and clinically feasible regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Furthermore, the results show that The results of the present trial confirm and extend published studies [2][3][4][5][6]9,10] in many aspects. Furthermore, the results show that The results of the present trial confirm and extend published studies [2][3][4][5][6]9,10] in many aspects.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, the results show that The results of the present trial confirm and extend published studies [2][3][4][5][6]9,10] in many aspects. Furthermore, the results show that The results of the present trial confirm and extend published studies [2][3][4][5][6]9,10] in many aspects.…”
Section: Resultssupporting
confidence: 91%
“…Prophylactic antimicrobials should be chosen to target these bacteria. The recommended antimicrobials to prevent UTIs after TUR‐Bt are injective CEPs and oral fluoroquinolones (FQLs) 16–20,22,28,30–35 . Attention to fluoroquinolone‐resistant Escherichia coli should be paid, however, because its prevalence has been reported 36 .…”
Section: Detailed Expositionmentioning
confidence: 99%
“…Postoperative UTIs and bacteremia were the typical complications of TUR‐P, so effective AMP is necessary. Many studies on the necessity of AMP for TUR‐P have been reported 3,13,14,46–89 . Among them, many randomized comparative studies and meta‐analysis 88,89 were included.…”
Section: Detailed Expositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, incidence of postoperative symptomatic UTIs was low in patients without using AMP. The incidence (3.4%) was equivalent to that (2.3%) in patients with single dose of fluoroquinolone, which some previous studies recommended as AMP for TURBT 1–6 . Moreover, these symptomatic UTIs were easily treated by deferred use of antibiotics.…”
Section: Discussionmentioning
confidence: 80%